Toxicity of Pesticides - Rao, K.S. (Biology, Engineering, Medicine and Science Reports)
All pesticides must be toxic, or poisonous, to be effective against the pests they are intended to con- trol. Because pesticides are toxic, they are potentially hazardous to humans, animals, other organisms and the environment. Therefore, people who use pesti- cides or regularly come in contact with them must understand the relative toxicity and potential health effects of the products they use.